Strategic Logistics on Halal Products - Siti Maemunah; Baehaqi Syakbani (Sekolah Tinggi Ilmu Ekonomi AMM, 2021)
This study introduces a new conceptual framework related to the logistics strategy of halal products on customer loyalty. The provision of halal products must be carried out in a Muslim country, namely Indonesia. Products that provide halal certification for these products are LPPOM MUI Indonesia Halal Products, LPPOM MUI, 2020. This methodological study was built and developed from several previous studies. This research is quantitative research with SEM. This finding is the importance of halal product logistics strategy and product quality will influence consumer behavior. Consumer behavior is related to customer satisfaction and customer loyalty. The logistics strategy of halal products, namely products such as food, beverages, medicines, and cosmetic ingredients, requires a good management system, quality will get consumer satisfaction and loyalty in consuming halal products. The implication of this research is the logistics strategy of halal products is not only from product quality to make consumers satisfied. Consumers will be satisfied in terms of distribution, storage, marketing, and overall sales. Halal product logistics strategy meets consumer and market desires. Strategies to create customer loyalty. The originality of the research is a logistics strategy for halal products that gives birth to customer satisfaction and loyalty. This study provides an important reference for Islamic companies, branding, and marketing.